Pendampingan Pembuatan Soft Candy Semangka, Nutrisi Halal Pemenuhan Zat Besi Sebagai Upaya Pencegahan Stunting - Vevi Maritha; Arum Suproborini; Puri Ratna Kartini; Desi Kusumawati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Prevalence of stunting in children in Indonesia at the national level is around 37%. Various efforts are made to reduce and prevent the incidence of stunting, one of the efforts to overcome this is the fulfillment of nutrition in children. one of the efforts to overcome this is the fulfillment of nutrition in children. One of One of the micronutrients that is important for child growth is iron. Lack of iron deficiency can cause stunting and impaired cognitive development in children. children. Iron is found in many foods, including watermelon. At Some people dislike the consumption of fruit directly. This becomes a challenge in itself where there needs to be an effort to process watermelon fruit into a dosage form that is favored by children, namely soft candy. One of one of the main ingredients for making soft candy is gelatin which needs to be considered its halalness. Therefore, there is assistance in making watermelon soft candy as halal nutrition to meet the iron needs of children as an effort to prevent stunting in MT Annisa, MT Annisa, MT Annisa, MT Annisa, MT Annisa. to prevent stunting in MT Annisa, Madiun City. The method in this activity begins with a pretest, then socialization and workshops, and ends with a posttest. The pretest results showed that only 9.09%, while the posttest results were 54.55% of residents who understood the knowledge and process of making halal watermelon soft candy for making halal watermelon soft candy for stunting prevention nutrition. This shows an increase in community knowledge after attending socialization and workshop looks different.